Solution of optimal capacitor placement problem using improved differential evolutionary algorithm on radial networks - Karimi, Mohammad; Shayeghi, Hossein (Видавництво Львівської політехніки, 2011)
The capacitor placement problem consists of determining the optimal numbers, types, locations and sizes of capacitor banks such that minimum yearly cost due to power/energy losses and cost of capacitors is achieved, while the operational and power quality constraints are maintained within the required limits. This paper has proposed several improvement steps on differential evolutionary algorithm (DE) for obtaining improved differential evolutionary (IDE) algorithm. The obtained IDE has used for optimal placement and sizing of capacitor in radial distribution networks. The proposal method has been tested on 10-bus IEEE standard network. To demonstrate sufficiency and reliability of proposed IDE, this compared with other approaches in valid references.
Вирішення проблеми оптимального розміщення конденсатора з використанням покращеного диференціального еволюційного алгоритму на радіальних мережах
Keywords: Optimal Capacitor Placement (OCP); Improved Differential Evolutionary Algorithm (IDE); Radial Distribution Systems